The Effect Of Video Media On Postpartum Mother’s Knowledge About IUD Contraception - Sry Wahyuni; Ummu Kalsum; Lina Fitriani; Masyitah Wahab (CV. Inara, 2023)
Couples of childbearing age are the targets of the family planning program, from the number of PUS there are some who decide they want to delay pregnancy or do not want additional children but do not use family planning, this EFA group is referred to as unmet need. Low knowledge causes women to be afraid to use contraceptives because previously rumors of contraception circulating in the community, as a result of lack of knowledge of PUS in choosing good contraception, negatively impacted attitudes and behavior in planning their next pregnancy. have a known problem with “4 Too”(4-T) (too many, too young, too old, too close in birth spacing) which is very dangerous. This condition is supported by the presence of three late (3T), namely being late in recognizing signs, being late in reaching the service center and being late in getting help. Factors (4T and 3T) are social problems that also determine the health and safety of the labor process and the rapid birth rate of babies. The research method used was pre-experimental with one-group pretest posttest design. This study used 15 samples based on inclusion criteria, the sampling technique was purposive sampling. The results showed that there was a difference in knowledge of post-test mothers which was higher than the results of mothers' knowledge on pre-test using video media on IUD contraception.